The effect of burned liver on the length, weight and development of Megaselia scalaris (Loew) (Diptera: Phoridae) – a preliminary assessment and implications in forensic entomology - Nur Aqidah Ahmad,; Amirah Suhailah Ramli,; Raja Muhammad Zuha Raja Kamal Bashah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Development of insects in laboratory for minimum post mortem interval estimation (mPMI) or time of colonisation (TOC) in forensic entomology can be affected by the type and quality of food consumed during larval period. Since mPMI estimation also involves analysis of larval specimens collected from burned human remains, it is important to study if burned tissues could affect growth of sarcosaprophagous larvae. This study investigated the effect of burned tissues on the size and developmental period of Megaselia scalaris (Loew) (Diptera: Phoridae), a species of forensic importance. Development of M. scalaris on 75 g burned cow’s liver was compared with control liver in three study replicates. Mean larval length (2.87 ± 0.11 mm) and weight (0.81 ± 0.08 mg) of M. scalaris larvae in burned liver diets were significantly lower than larval length (5.03 ± 0.15 mm) and weight (2.85 ± 0.21 mg) of control liver diets (p < 0.001) whilst mean pupal length (2.53 ± 0.06 mm) and weight (0.92 ± 0.06 mg) in burned liver diets were significantly lower than pupal length (3.52 ± 0.06 mm) and weight (2.84 ± 0.16 mg) in control liver diets (p < 0.001). Development of larvae in burned liver was 5-9 hours slower than those feeding on control liver based on single observation. Although the assessment is preliminary, the findings indicate physical growth of larvae feeding on burned animal tissues was affected and entomological specimens recovered from burned remains should be evaluated carefully to avoid errors in mPMI/TOC estimation. Limitations and suggestions for further research are also presented herein